Theoretical analysis of the energy levels induced by oxygen vacancies and the doping process (Co, Cu and Zn) on SnO2 (110) surface models - Sensato, F. R.; Filho, O. T.; Longo, Elson [UNESP]; Sambrano, JR; Andres, J. (Elsevier B.V., 2001)
Density functional calculation at B3LYP level was employed to study the surface oxygen vacancies and the doping process of Co, Cu and Zn on SnO2 (110) surface models. Large clusters, based on (SnO2)(15) models, were selected to simulate the oxidized (Sn15O30), half-reduced (Sn15O29) and the reduced (Sn15O28) surfaces. The doping process was considered on the reduced surfaces: Sn13Co2O28, Sn13Cu2O28 and Sn13Zn2O28. The results are analyzed and discussed based on a calculation of the energy levels along the bulk band gap region, determined by a projection of the monoelectron level structure on to the atomic basis set and by the density of states. This procedure enables one to distinguish the states coming from the bulk, the oxygen vacancies and the doping process, on passing from an oxidized to a reduced surface, missing bridge oxygen atoms generate electronic levels along the band gap region, associated with 5s/5p of four-/five-fold Sn and 2p of in-plane O centers located on the exposed surface, which is in agreement with previous theoretical and experimental investigations. The formation energy of one and two oxygen vacancies is 3.0 and 3.9 eV, respectively. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: tin oxide; clusters; surface electronic phenomena; surface defects; B3LYP hybrid functional